The Effect of Verbal, Visual, and Combined Instructions on Learning a Sports Skill: An Effective Instruction Approach for Enhancing Adolescent Sports Performance - Salehi, Sayed Kavos; Hatami, Farzaneh; Godarzi, Zahra (International Journal of Sport Studies for Health, 2025)
Objective: The purpose of this study was to investigate the effect of verbal, visual and combined instructions on learning the simple forehand service skill of table tennis. Materials and Methods: To achieve the objectives of the study, 36 right-handed female adolescents, aged between 14 and 16 years, were selected through convenience sampling and took part in the study. The study consisted of six phases including familiarity, pre-test, acquisition, post-test, retention, and transfer. During the familiarity phase, brief explanations about the criterion skill were provided. In the pre-test stage, each participant performed one block of 10 trials of the criterion skill. The acquisition phase included four sessions that in each session, participants—based on their assigned group (verbal, visual, or combined)—practiced three blocks of 10 trials of the skill. Immediately after completing the acquisition phase, the post-test was conducted, consisting of one block of 10 trials. The retention and transfer tests were administered 24 hours after the acquisition phase. Data were analyzed using descriptive and inferential statistical methods. Findings: The results indicated that the combined instruction group showed significant improvement in acquiring the forehand simple serve skill (p < 0.05), while the verbal and visual groups did not exhibit significant changes. Additionally, in the retention and transfer stages, the combined group outperformed the other two groups, highlighting the positive effect of combined instruction on more stable learning and more effective skill transfer. Conclusion: The results suggest that the combined instruction approach led to more stable learning and more effective transfer of the forehand simple serve skill in table tennis. This highlights the efficacy of combined verbal and visual instructions in enhancing adolescent sports performance.